Frequency Determination of Carbapenem-Resistant Klebsiella Pneumoniae (CRKP) Isolated from hospitals in Isfahan of Iran and Evaluation of Synergistic Effect of Colistin and Meropenem on them - Gheitani, Leila; Fazeli, Hossein; Moghim, Sharareh; Nasr Isfahani, Bahram (Cellular and Molecular Biology, 2018)
Overuse and misuse of Carbapenems among Klebsiella pneumoniae isolates have caused Carbapenem-Resistant Klebsiella Pneumonia (CRKP) during recent years. Colistin is one of the last available options, and there are increasing concerns about the dosage and resistance to this agent in long-term monotherapies. This study was designed to identification of carbapenemase producing isolates of K. pneumoniae via phenotypic and genotypic methods as well as evaluation of colistin-meropenem combination therapy potential. This study was carried out in Isfahan, of Iran on 100 samples from Alzahra and Khorshid hospitals in 2017. The Modified Hodge Test (MHT) was used to investigate the carbapenemase presence. The minimum inhibitory concentration (MIC) and the Fractional Inhibitory Concentration (FIC) were determined using broth macrodilution and checkerboard assays (respectively) for both meropenem and colistin. The bla-KPC gene was studied by polymerase chain reaction (PCR).The highest and the lowest rate of resistance were observed for piperacillin (84%) and ertapenem (50%) respectively. 68 isolates by MHT were CRKP, but None of them were positive for bla-KPC gene. 21 isolates from CRKP cases were high resistant to used antimicrobial agents in the study that both MIC and FIC results showed significant synergy for this antibiotics in checkerboard test (p-value < 0.05). 21 resistant isolates from CRKP cases showed statistically significant synergy potential for meropenem and colistin. The meropenem-colistin combination therapy can be applied as a suitable antibiotic synergy but it requires further investigation in clinical assay. Regarding to our findings, Probably other mechanisms of resistance to Carbapenems ,except bla-kpc genes are involved.